Evaluasi Pemilihan Kepala Daerah di Kota Jambi - Nuraini, Nuraini; Masriyani, Masriyani (Legalitas: Jurnal Hukum, 2025)
This study aims to evaluate the implementation of the 2024 Regional Head Election (Pilkada) in Jambi City as a reflection of democratic principles at the local level. Although the election was administratively conducted in accordance with statutory provisions, voter participation remained below the national target, reaching only 62% of the final voter list. Using a normative juridical approach and literature review methodology, this study examines legal regulations and relevant secondary data. The findings reveal substantial challenges such as weak political socialization, human error in technical procedures, vote buying, civil servant involvement in campaigns, and suboptimal internal supervision by the KPU. Therefore, there is an urgent need to strengthen the substantive aspects of democracy and reformulate the electoral mechanism to ensure a more participatory, fair, and integrity-based election process